Acute genetic perturbation of exocyst function in the rat calyx of Held impedes structural maturation, but spares synaptic transmission - Schwenger, Darius; Kuner, Thomas (European journal of neuroscience, 2010)
The exocyst is an octameric protein complex mediating polarized secretion by tethering vesicles to target membranes. In non-vertebrate neurons, the exocyst has been associated with constitutive membrane addition at growth cones and nerve terminals, but its function in synaptic vesicle trafficking at mammalian nerve terminals remains unclear. Here, we examined the role of the exocyst complex in immature postnatal day (P)13 and mature P21 rat calyces of Held. ...